2009
DOI: 10.1088/0957-4484/20/21/215701
|View full text |Cite
|
Sign up to set email alerts
|

Computational studies on hydrogen storage in aluminum nitride nanowires/tubes

Abstract: One-dimensional AlN nanowires/tubes were exploited as hydrogen storage media. The adsorption of atomic and molecular hydrogen on AlN nanowires was investigated by using density functional theory computations. Hydrogen atoms prefer to adsorb on top of neighboring threefold-coordinated N and Al atoms in pairs. A hydrogen molecule, however, prefers to adsorb on top of threefold-coordinated Al atoms in the nanowire surface, with an adsorption energy of 0.21 eV. H(2) dissociation is exothermic in the surface of AlN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 64 publications
(70 reference statements)
1
10
0
Order By: Relevance
“…Further, device applications of AlN as an optoelectronic and field-emission material could largely benefit from the accomplishment of crystallographically perfect lowdimensional objects such as AlN nanowires. AlN nano-wires [11,12] and AlN nanoribbons [13] have been fabricated and characterized, while computational studies identify AlN nanowires/tubes as a prospective hydrogen storage media [14]. The h-AlN sheet considered in this work represents a prospective low-dimensional object with specific properties for which we perform first-principles calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Further, device applications of AlN as an optoelectronic and field-emission material could largely benefit from the accomplishment of crystallographically perfect lowdimensional objects such as AlN nanowires. AlN nano-wires [11,12] and AlN nanoribbons [13] have been fabricated and characterized, while computational studies identify AlN nanowires/tubes as a prospective hydrogen storage media [14]. The h-AlN sheet considered in this work represents a prospective low-dimensional object with specific properties for which we perform first-principles calculations.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies on fabrication and characterization of AlN nanostructures have been reported. [1][2][3][4][5][6][7] Several promising applications such as field emitters, [8][9][10][11] hydrogen storage media, 12,13 light emitting devices, [14][15][16] and photo detectors 17 have been demonstrated. AlN nanorods also served as the barrier layer in GaN/AlN quantum dots/wire system for single photon source owing to the strong confinement of electron-hole pair as a result of its large band offset.…”
mentioning
confidence: 99%
“…The electron exchange correlation is treated within the generalized gradient approximation (GGA) with PW91 functional [39]. Also, local density approximation (LDA) with CA functional [40] was employed to evaluate the hydrogen molecule adsorption energies and compare with the GGA results, as previous studies showed that GGA usually underestimates the H 2 adsorption energy, whereas LDA overestimates the interaction [24,[41][42][43], and the real value may be located in the range between GGA and LDA results; therefore, GGA and LDA results are widely adopted to evaluate the range of the hydrogen adsorption energies before better methodologies appear. Meanwhile, the electron-ion interactions are modeled by the ultrasoft pseudopotentials [44].…”
Section: Methodsmentioning
confidence: 99%